TINGKAT PENGETAHUAN DAN SIKAP ORANG TUA YANG MEMILIKI ANAK AUTIS TENTANG TUMBUH KEMBANG ANAK AUTIS DI KLINIK FADIRA BINJAI TAHUN 2018 - Nurhafni Nurhafni (Poltekkes Kemenkes Medan, 2020)
Growth is increasing in size and the cell size of all parts of the body, development is increasing body structure and function that is more complex in the ability to coarse motion, smooth motion, speech and language and socialization and independence. Autism is a neurobiological development disorder that is very complex / long in life, which includes disturbances in aspects of social interaction, communication and language, and behavior and emotional disturbances and sensory perceptions even in the motor aspects. Autistic symptoms appear before 3 years of age. Knowledge is the result of